Experimental and numerical evaluation of anisotropic fill performance characteristics in cross- and counterflow - Grobbelaar, Pieter Jacobus (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--Stellenbosch University, 2012.